A influência de fatores na produtividade do desenvolvimento de software de acordo com um modelo de estruturas teóricas - Chapetta, Wladmir Araujo (2018)
This work presents an evidence-based model describing the effects of a set of factors on software development productivity, obtained through an evidence synthesis method in Software Engineering. Thus, the relationships among this set and the software development productivity (observed phenomena) are described as results of combining theoretical structures capable of expressing and dealing with differences between different effects and uncertainties varying according to the types of studies found in the literature. Besides, to evaluate the model found, its findings are confronted with a survey capturing the practitioners’ perception (managers and leaders of software projects in Brazilian organizations). The degree of agreement between research (the model) and practice (the practitioners’ perception) shows that scientific knowledge does not differ considerably from the reality experienced by software projects when both of them refer to the influence of factors on software development productivity. The impression that research and practice on the theme go through different paths persists. According to this work, the reasons for this impression are more related to the use of non-standardized and, perhaps, inappropriate measures used to perceive and monitor the influence of factors as well as to measure the software development productivity